Health care costs : causes, effects and control - Hofmann, Bernice R. (Health care issues, costs, and access., 2009)
"It is difficult to find an area of such unyielding cost increases as health care except perhaps energy costs. These costs and the underlying health care systems continue to constitute major issues around the world. This new book tackles these tough issues head on from multiple perspectives around the world."--Publisher's description